Model Pemberdayaan Ekonomi Masyarakat Lokal Dalam Meningkatkan Pendapatan Melalui Pasar Krempyeng dan Peran Pemerintah Ponorogo Ditinjau Dari Perspektif Ekonomi Islam (in press) - sri, titiksriwinih (Jurnal Iqtisaduna, 2023)
The model for empowering the Ponorogo district government in empowering the local community's economy through the krampyeng market is viewed from an Islamic economic perspective. This activity at the Krempyeng market is a form of economic empowerment model for local communities in order to prosper, improve and revive the economy of the Ponorogo area, especially in rural areas or sub-districts. The enthusiasm of the Ponorogo district government regarding the krampyeng market is that the Chairperson of the Empowerment and Family Welfare Mobilization Team (TP PKK) has the role of facilitator, planner, implementer, controller and activator at each level for the implementation of the PKK program. In leading an area, as a leader Ponorogo Regency when viewed from an Islamic economic perspective is in accordance with conceptual leadership such as the basis of monotheism, leader responsibility, justice, equality among fellow Muslims, deliberation. The krampyeng market program has an impact in the economic, social and cultural fields. Keywords: empowerment, krampyeng market, role of government, Islamic economics